The Use of Batavia language in South Jakarta (Study of sociodialectology) - Nur Irwansyah; Sri Mulyani,; Reni Rokhayati (Universitas Indraprasta PGRI, 2017)
This research is intended to describe some use of Betawi Language for it is native, it is speaker or those who have lived in South Jakarta for more than ten years through sociodialectology. This research scoops two goals which are (1) to describe the use of Betawi language phonologically and lexically (2) to determine similarities and differences of Betawi Language in South Jakarta.Method used in this research is descriptive comparative method. This method is suitable to compare language rolesimilarities, dialect similarities, and dialect differences in Srengseng Sawah and Ciganjur as subdistricts of Jagakarsa, Pejaten Barat as subdistricts of Pasar Minggu, Lebak Bulus and South Gandaria as subdistricts of Cilandak through phonology and lexical level.Betawi Language contents many similarities and differences. Both cover either wholly or partially. This goes for a shortcut that each area has it is lexical and referent. Beyond that, there are two areas having differences amongst others. Yet, by statistic calculation using dialectometry, we conclude that differences occur in subdialect level.